Doing death work: a typology of how homicide detectives orient to their work - Dabney, Dean (Policing and society, 2020)
Homicide investigation is among the most prestigious and challenging undertakings in modern day law enforcement agencies. Most metropolitan police departments assign the investigation of suspicious deaths to a dedicated homicide unit staffed by an elite group of specially trained and highly competent investigators. These units are commonly associated with close-knit cultures, high individual and collective expectations, and high status within the organisation. Drawing upon roughly 300 hours of ethnographic work within the homicide unit of a major metropolitan police department in the US, this paper provides insight into how homicide investigators construct their occupational identities within the context of their work environment. A 4-part typology of homicide detective identities emerged from the data with one’s primary motivation for solving cases and general approach to investigative work shaping membership outcomes. The theoretical and policy implications that follow are considered, especially the way that detectives orient to their work and its potential impact on homicide casework and clearance levels.